2004
DOI: 10.1038/sj.bjp.0705659
|View full text |Cite
|
Sign up to set email alerts
|

Regional haemodynamic effects of cyclosporine A, tacrolimus and sirolimus in conscious rats

Abstract: 1 The observation that the immunosuppressants, cyclosporine A (CsA) and tacrolimus, have pressor effects, but sirolimus does not, has led to an hypothesis that generalised sympathoexcitation, resulting from inhibition of calcineurin by CsA and tacrolimus underlies their pressor effects, because sirolimus does not inhibit calcineurin. It is unknown if sirolimus has haemodynamic actions not accompanied by a pressor effect, and whether or not the pressor effects of CsA and tacrolimus are accompanied by similar ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 44 publications
1
30
2
Order By: Relevance
“…Animal studies have demonstrated that the vasoconstrictive effect of tacrolimus is weaker than of cyclosporine (205)(206)(207), and this was also confirmed in humans (208,209). Moreover, the fibrogenic potential of tacrolimus also appears to be lower (210), although these results could not be confirmed in a more recent study (135).…”
Section: Comparison Between Cyclosporine and Tacrolimusmentioning
confidence: 98%
“…Animal studies have demonstrated that the vasoconstrictive effect of tacrolimus is weaker than of cyclosporine (205)(206)(207), and this was also confirmed in humans (208,209). Moreover, the fibrogenic potential of tacrolimus also appears to be lower (210), although these results could not be confirmed in a more recent study (135).…”
Section: Comparison Between Cyclosporine and Tacrolimusmentioning
confidence: 98%
“…Under in vivo conditions, however, i.v. injection of sirolimus into conscious rats caused a modest pressor response and decrease in regional blood flow (Gardiner et al, 2004), consistent with a vasoconstrictor effect. In light of the present results demonstrating that sirolimus causes endothelium-independent relaxation of human arteries, the importance of species differences and the need to assess the pharmacologic activity of vasoactive drugs in human tissues are readily apparent.…”
Section: Discussionmentioning
confidence: 62%
“…This is particularly notable since sirolimus is released directly into the circulation (Hiatt et al, 2001;Suzuki et al, 2001), where it could potentially alter blood flow and tissue perfusion in regions distal to the site of stent placement. A limited number of preliminary studies have attempted to address this issue by using animal models, but the results are conflicting (Corbin et al, 1994;Milliard et al, 1998;Jeanmart et al, 2002;Gardiner et al, 2004). Hence, the present study was designed to determine the vasomotor effects of sirolimus in human blood vessels.…”
mentioning
confidence: 99%
“…When given by bolus i.v. injection, FK506 causes a pressor effect, which is maximal when there is no significant regional vasoconstriction in conscious rats (25).…”
Section: Discussionmentioning
confidence: 97%
“…Alternatively, increased or impaired vascular reactivity caused by FK506 was unlikely to be the sole explanation for its hypertensive side effect. Gardiner et al (25) have reported that the blood pressure increasing effect of FK506 must be due to an increase in cardiac output. When given by bolus i.v.…”
Section: Discussionmentioning
confidence: 99%